Students' Understanding of Online History Learning in Senior High School - Lisda Triana; Muhamad Abi Fadila; Rama Aditia Nugroho; Andi Andi (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to describe students' understanding of historical learning in online learning in high school, the results of research in analysis using cognitive theory, then research methods using qualitative methods using case study approach. Techniques used in conducting research and data collection using observation and interview techniques. The results showed that the transition from offline learning methods to online learning is quite affecting the effectiveness of teachers in delivering their material to students, where not all lessons can easily adapt to the transition of offline learning to online learning, one of which is history that at first students have a little difficulty to absorb and understand the learning done offline, but with the application of online learning due to covid-19 is enough to make it difficult for students to digest materials in online history learning.